Effectiveness of Kangaroo Mother Care in Establishing Breastfeeding in Preterm Low Birth Neonates - Mushtaq, Misbah; Munir, Minahil; Fazal, Fariha; Shaukat, Rabia; Khurshid, Asim; Malik, Abdul Rehman (Biological and Clinical Sciences Research Journal, 2025)
The establishment of breastfeeding in preterm and low birth weight infants is often challenging due to immature physiological mechanisms and maternal difficulties. Objectives: To evaluate the effectiveness of kangaroo mother care in establishing successful first breastfeeding in preterm low birth weight neonates compared to standard care. Methods: This randomized controlled trial was conducted in the Department of Pediatrics at the Children's Hospital, Multan, over 6 months from January 2024 to June 2024, following CPSP synopsis approval. A total of 182 preterm, low-birth-weight infants were enrolled through nonprobability, consecutive sampling and randomly allocated to two equal groups. Group A received standard care under a radiant warmer, while Group B received KMC as per WHO guidelines. Successful first breastfeeding was defined as initiation of breastfeeding within two hours of delivery with an Infant Breastfeeding Assessment Tool (IBFAT) score >8. Data were analyzed using SPSS version 23. The chi-square test was applied, and the maternal and neonatal characteristics stratified results; significance was set at p < 0.05. Results: Successful first breastfeeding was achieved in 41 (45.1%) infants in Group A and 58 (63.7%) in Group B, with a statistically significant difference (p = 0.012). Stratified analysis revealed greater effectiveness of KMC among younger mothers, infants of lower gestational age, infants with lower birth weight, male infants, lower gravida, and infants with SVD deliveries. Conclusion: Kangaroo mother care was significantly more effective than standard care in establishing successful first breastfeeding in preterm low birth weight neonates. Routine adoption of KMC is recommended to improve neonatal feeding outcomes.